Individual and joint associations of genetic risk and healthy lifestyle score with colorectal neoplasms among participants of screening colonoscopy - Erben, Vanessa; Carr, Prudence R.; Guo, Feng; Weigl, Korbinian; Hoffmeister, Michael; Brenner, Hermann (Cancer Prevention Research, 2021)
Genetic and lifestyle factors contribute to colorectal cancer risk. We investigated their individual and joint associations with various stages of colorectal carcinogenesis. We assessed associations of a polygenic risk score (PRS) and a healthy lifestyle score (HLS) with presence of nonadvanced adenomas and advanced neoplasms among 2,585 participants of screening colonoscopy from Germany. The PRS and HLS individually showed only weak associations with presence of nonadvanced adenomas; stronger associations were observed with advanced neoplasms (ORs, 95% CI, for highest vs. lowest risk tertile: PRS 2.27, 1.78-2.88; HLS 1.96, 1.53-2.51). The PRS was associated with higher odds of advanced neoplasms among carriers of any neoplasms (1.65, 1.23-2.22). Subjects in the highest risk tertile (vs. lowest tertile) of both scores had higher risks for nonadvanced adenomas (1.77, 1.09-2.86), for advanced neoplasms (3.95, 2.53-6.16) and, among carriers of any neoplasms, for advanced versus nonadvanced neoplasms (2.26, 1.31-3.92). Both scores were individually associated with increased risk of nonadvanced adenomas and, much more pronounced, advanced neoplasms. The similarly strong association in relative terms across all levels of genetic risk implies that a healthy lifestyle may be particularly beneficial in those at highest genetic risk, given that the same relative risk reduction in this group would imply a stronger absolute risk reduction. Genetic factors may be of particular relevance for the transition of nonadvanced to advanced adenomas. - Prevention Relevance: Genetic factors have strong impact on the risk of colorectal neoplasms, which may be reduced by healthy lifestyle. Similarly strong associations in relative terms across all levels of genetic risk imply that a healthy lifestyle may be beneficial due to higher absolute risk reduction in those at highest genetic risk.
Published online first March 2, 2021
Gesehen am 03.08.2021